2009
DOI: 10.1161/circulationaha.109.849828
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Cardiovascular Magnetic Resonance in the Diagnosis of Anderson-Fabry Disease

Abstract: A 54-year-old man was evaluated for a 6-month history of intermittent palpitations with associated shortness of breath, fatigue, and lightheadedness. The episodes would last several hours and were triggered by exertion, although he never experienced syncope. He had no prior medical problems, and he had no family history of heart disease or unexplained sudden death.He was normotensive and had no abnormalities on physical examination. A 12-lead electrocardiogram showed sinus arrhythmia, left bundle-branch block,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…In patients with Anderson-Fabry disease, it has been reported that approximately half have LGE localized to the mid-myocardial portion of the basal inferolateral wall, sparing the subendocardium (191), a location and distribution of LGE that may help distinguish this disease from other forms of nonischemic cardiomyopathies such as HCM (189). Patterns of LGE in HCM are heterogeneous, may occur commonly in either the ventricular septum or LV free wall, and usually involve segments of the chamber that are most hypertrophied and do not conform to particular coronary arterial distributions (185).…”
Section: Cardiac Magnetic Resonancerecommendationsmentioning
confidence: 99%
“…In patients with Anderson-Fabry disease, it has been reported that approximately half have LGE localized to the mid-myocardial portion of the basal inferolateral wall, sparing the subendocardium (191), a location and distribution of LGE that may help distinguish this disease from other forms of nonischemic cardiomyopathies such as HCM (189). Patterns of LGE in HCM are heterogeneous, may occur commonly in either the ventricular septum or LV free wall, and usually involve segments of the chamber that are most hypertrophied and do not conform to particular coronary arterial distributions (185).…”
Section: Cardiac Magnetic Resonancerecommendationsmentioning
confidence: 99%
“…Only a few female patients were included in these clinical studies (11,12). Moreover, subtle methods of assessing cardiac function with echocardiography (strain rate) or detecting replacement fibrosis with cardiac magnetic resonance (CMR) (late enhancement [LE]) (11)(12)(13)(14)(15)(16)(17)(18)(19) have not been used in studies focusing on Fabry cardiomyopathy in female patients (8,20). Up to now, there has been no established guideline how to monitor female patients and when (at which stage of the disease) to treat these patients with cardiac involvement caused by Fabry disease.…”
mentioning
confidence: 99%
“…Taking into account these results, we should stress the importance to perform CMR to stage and monitor Fabry cardiomyopathy, after diagnosis in both genders, even in apparently asymptomatic patients with a normal echocardiogram. CMR can be also fundamental in the diagnostic process of patients evaluated for cardiomyopathy, as LGE in the midmyocardium of the basal-inferolateral wall seems to be characteristic of Fabry disease [12]. It should be acknowledged that LGE in the midmyocardium of the basal-inferolateral wall can also be observed in other pathologies, including previous myocarditis [13].…”
Section: Discussionmentioning
confidence: 99%